Chủ quyền carbon: Cơ sở lý luận và hàm ý chính sách phát triển thị trường carbon Việt Nam - Phạm Khánh , Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The carbon market is a key policy instrument to help Vietnam achieve its greenhouse gas emission reduction commitments under the Nationally Determined Contribution (NDC) and its goal of net-zero by 2050. However, current legal documents and regulations on the carbon market mainly address its general structure, without establishing a foundational approach for building an effective and sustainable carbon market. This study proposes "carbon sovereignty" as a core approach for developing the carbon market, aiming to optimize economic opportunities from carbon transactions, protect national interests in international negotiations, and contribute to the achievement of long-term sustainable development goals. The paper reviews the theoretical foundations of carbon sovereignty and discusses its potential applications in Vietnam. The main pillars of the carbon sovereignty approach include a mandatory carbon market, a regulated voluntary carbon credit market, digitalization of the national registry system, and digitalization of carbon credits.